2010
DOI: 10.1345/aph.1m576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a tele-ICU Pharmacist on the Management of Sedation in Critically III Mechanically Ventilated Patients

Abstract: Tele-ICU resources can be utilized to increase compliance with an established ICU sedation guideline and extend the benefits that daytime ICU clinical pharmacy services provide. Increased ICU pharmacist availability may have additional benefits not measured in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 15 publications
4
43
0
Order By: Relevance
“…For example, a recent cluster-randomized trial showed that a multifaceted knowledge-translation intervention that included education via telemedicine increased the adoption of targeted best practices in community hospitals with few resources dedicated to quality improvement [34]. Similarly, a before/after study found a significant increase in the percentage of patients who received a daily sedative interruption with tele-ICU pharmacy support [35]. Last, one study reported improved nursing-staff satisfaction after the implementation of robotic tele-ICU [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent cluster-randomized trial showed that a multifaceted knowledge-translation intervention that included education via telemedicine increased the adoption of targeted best practices in community hospitals with few resources dedicated to quality improvement [34]. Similarly, a before/after study found a significant increase in the percentage of patients who received a daily sedative interruption with tele-ICU pharmacy support [35]. Last, one study reported improved nursing-staff satisfaction after the implementation of robotic tele-ICU [36].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] This definition covers a variety of tele-ICU models ranging from exclusively reactive systems, where tele-ICU staff was available via telephone on an as-needed consultative basis, 27 to the more commonly used proactive systems, where patients were continuously monitored in real time via videoconferencing, telemetry, and access to the electronic medical record. 28,29 …”
Section: Study Inclusion Criteria and Outcome Measuresmentioning
confidence: 99%
“…Current examples of telehealth programs with clinical pharmacist involvement include cardiology, diabetes, and anticoagulation in the VA and HIV and hepatitis C in the Department of Corrections . Table provides information on settings where clinical pharmacists have successfully implemented and used telehealth care practices . With the continued expansion of telehealth, development of postgraduate training programs will likely follow.…”
Section: Methodsmentioning
confidence: 99%
“…53,54 Table 3 provides information on settings where clinical pharmacists have successfully implemented and used telehealth care practices. [51][52][53][55][56][57][58][59][60] With the continued expansion of telehealth, development of postgraduate training programs will likely follow.…”
Section: Methodsmentioning
confidence: 99%